2013
DOI: 10.4048/jbc.2013.16.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes of Standard and Oncoplastic Breast-Conserving Surgery

Abstract: PurposeThe aim of this study is to determine and to compare the oncological outcomes of bilateral reduction mammoplasty to standard breast-conserving surgery for breast cancer.MethodsOne hundred sixty-two patients who received a quadrantectomy because of breast cancer (group 1) and 106 breast cancer patients with macromastia who underwent breast-conserving surgery via bilateral reduction mammoplasty (group 2) between 2003 and 2010 were enrolled in this study.ResultsThe mean follow-up time was 37 months for gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…15 comparative studies have been published which report on results following OBCS (Table 3) [8,16e21,24,25,28e33]. Of those, 9 papers reported various aspects of oncological outcomes [8,16e21,24,30], but recurrence rates and survival e the ultimate measures of oncological safety e were detailed in three comparative studies only [8,21,30]. OBCS was compared to standard breast conservation techniques (WLE or quandrantectomy) in almost all studies (Table 3.).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…15 comparative studies have been published which report on results following OBCS (Table 3) [8,16e21,24,25,28e33]. Of those, 9 papers reported various aspects of oncological outcomes [8,16e21,24,30], but recurrence rates and survival e the ultimate measures of oncological safety e were detailed in three comparative studies only [8,21,30]. OBCS was compared to standard breast conservation techniques (WLE or quandrantectomy) in almost all studies (Table 3.).…”
Section: Discussionmentioning
confidence: 98%
“…The current evidence for the oncological safety of OBCS is largely based on single-institution uncontrolled retrospective studies along with a few comparative studies where OBCS outcomes are compared to simple WLE or quadrantectomy [2,6e23]. The majority of studies showed similar pathological characteristics in terms of size, grade, subtype, hormone receptor expression and axillary node metastasis [17,18,21,24,25], although some demonstrated that larger tumour size, presence of invasive cancer and axillary nodal metastasis were more common following OBCS [8,19,20]. In these analyses OBCS was compared with WLE exclusively, but a comparison to mastectomy may have been appropriate, too, since more advanced pathology was demonstrated after OBCS.…”
Section: Introductionmentioning
confidence: 98%
“…The other breast may be included in surgical procedures performed on patients with ptosis and macromastia to achieve symmetry. In addition to the benefits of dualsided reduction mammoplasty (oncoplastic reduction), a significant number of macromastia complaints are corrected as well [10]. OBCS often achieves a better esthetic result, as it preserves the natural boundaries of the breast and protects the skin [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…As in the current case, the radiation-induced deformities and scarring can be difficult to manage, usually requiring secondary reconstruction [5, 6]. …”
Section: Discussionmentioning
confidence: 99%